2006
DOI: 10.1063/1.2363233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dislocations on electrical and electron transport properties of InN thin films. I. Strain relief and formation of a dislocation network

Abstract: Articles you may be interested inImpact of varying buffer thickness generated strain and threading dislocations on the formation of plasma assisted MBE grown ultra-thin AlGaN/GaN heterostructure on silicon AIP Advances 5, 057149 (2015); 10.1063/1.4921757 Improved electron mobility in InSb epilayers and quantum wells on off-axis Ge (001) substratesThe strain-relaxation phenomena and the formation of a dislocation network in 2H-InN epilayers during molecular beam epitaxy are reported. Plastic and elastic strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 73 publications
4
48
0
Order By: Relevance
“…Prior work has found that the dislocation density is often nonuniform through the thickness of InN films. 17 Typically, the dislocation density drops rapidly within the first few hundred nanometers of the film/buffer interface before reaching a constant value. Sample A is sufficiently thin such that the dislocation density has not reached the typical asymptotic value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has found that the dislocation density is often nonuniform through the thickness of InN films. 17 Typically, the dislocation density drops rapidly within the first few hundred nanometers of the film/buffer interface before reaching a constant value. Sample A is sufficiently thin such that the dislocation density has not reached the typical asymptotic value.…”
Section: Resultsmentioning
confidence: 99%
“…Because InN growth is exclusively heteroepitaxial, usually on GaN, threading dislocation (TD) densities in InN are very high, typically in the range of 10 9 − 10 11 cm −2 . [15][16][17] It is clear at least qualitatively that dislocations play a role in limiting electron transport in n-type InN. For example, studies of non-radiative recombination 18 and of electron transport (mobility) 14,19,20 have found deleterious effects which are attributed to charged dislocations.…”
Section: -14mentioning
confidence: 99%
“…35 Any form of N-O bonding will appear in the spectra at higher binding energy with respect to the main peak (396.4 eV), i.e., the shoulder peak can be attributed to the presence of In-O bond. 36,37 XPS-measured valence band spectrum of HCPA-ALD grown sample was obtained in order to extract information about electronic structure of the InN sample (Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that dislocations act as donors and may indeed act as junction shunts in these materials as well, providing a plausible explanation for why the depletion region fails to fully isolate the p-type bulk from the n-type surface layer [17,27,[49][50][51][52][53][54][55][56][57].…”
Section: Baars Et Al Use a Parallel Conduction Model In Which The Obmentioning
confidence: 99%